2008
DOI: 10.1007/s10562-008-9628-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Individual Reactions of Hydrodesulphurization of Dibenzothiophene and Hydrogenation of 2-Methylnaphthalene on ZnNiMo/γ-Alumina Catalysts

Abstract: A series of ZnNiMo/c-alumina catalysts with variable Zn/(Ni ? Zn) ratio were synthesized. These catalysts were characterized by chemical analysis, temperature programmed reduction (TPR) and BET surface area. After that, these catalysts were tested in the individual reactions of hydrodesulphurization (HDS) of dibenzothiophene (DBT) and hydrogenation (HYD) of 2-methylnaphthalene (2MN). The results showed an increment of the catalytic activity, for both reactions, when the catalysts were doubly promoted with Ni a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…The second peak, a very broad and shorter peak with a maximum at 800°C was attributed to Mo species, much more difficult to reduce in tetrahedral sites or reduction of Mo 4? to metallic Mo [4,5]. This peak could also involve the reduction of Co species and ZnO on solid surface.…”
Section: Characterization Of Oxidized Catalytic Precursorsmentioning
confidence: 96%
See 1 more Smart Citation
“…The second peak, a very broad and shorter peak with a maximum at 800°C was attributed to Mo species, much more difficult to reduce in tetrahedral sites or reduction of Mo 4? to metallic Mo [4,5]. This peak could also involve the reduction of Co species and ZnO on solid surface.…”
Section: Characterization Of Oxidized Catalytic Precursorsmentioning
confidence: 96%
“…Some of these promoters have shown electronic effects as well as geometric effects; for instance Zn. Zn has been widely used as a structural promoter on (Co-(or Ni-) Mo)/calumina) catalysts, and it has been reported a marked synergetic effect in hydrodesulphurization (HDS) reactions [3][4][5][6][7][8][9]. The partial addition of Zn to traditional catalysts (CoMo/c-alumina and NiMo/c-alumina) is an easy way to synthesize cheaper catalysts (due to partial substitution of Ni or Co by Zn) and to improve successfully their catalytic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the HDS activity upon modifying the support with Zn additive is related according to the literature data [5,11] to the formation of spinels of the ZnAl 2 O 4 type which reduce the formation of Со(Ni)Al 2 O 4 spinels. In this case, a greater number of promoter atoms decorate MoS 2 layers forming a greater amount of the active sulfide phase Co(Ni)MoS.…”
Section: Resultsmentioning
confidence: 55%
“…It was shown that the intro duction of 0.2-0.4% ZnO in NiМo/Al 2 O 3 catalyst prepared by coextrusion using ammonium paramo lybdate [10] results in an increase in its HDS activity; the publication relates to diesel fuel hydrotreating cat alysts. In a work of Linares [5] it is reported that the addition of a small amount of Zn increases HDS activ ity. Strohmeier et al [11] also noted an increase in HDS activity upon addition of zinc in an amount up to 20%.…”
mentioning
confidence: 99%
See 1 more Smart Citation